Control of the onset of puberty. Issue 4 (August 2016) - Livadas, Sarantis; Chrousos, George P.
Abstract : Purpose of review: The mechanism of puberty initiation remains an enigma, despite extensive research in the field. Pulsatile pituitary gonadotropin secretion under the guidance of hypothalamic gonadotropin-releasing hormone (GnRH) constitutes a sine qua non for pubertal onset. In turn, the secretion of GnRH in the human hypothalamus is regulated by kisspeptin and its receptor as well as by permissive or opposing signals mediated by neurokinin B and dynorphin acting on their respective receptors. These three supra-GnRH regulators compose the Kisspeptin, Neurokinin B and Dynorhin neurons (KNDy) system, a key player in pubertal onset and progression. Recent findings: The recent discovery that makorin ring finger protein 3 is also involved in puberty initiation provided further insights into the regulation of the KNDy pathway. In fact, the inhibitory (γ-amino butyric acid, neuropeptide Y, and RFamide-related peptide-3) and stimulatory signals (glutamate) acting upstream of KNDy called into question the role of makorin ring finger protein 3 as the gatekeeper of puberty. Meanwhile, the findings that 'neuroestradiol' produced locally and endocrine disruptors from the environment may influence GnRH secretion is intriguing. Finally, epigenetic mechanisms have been implicated in pubertal onset through recently discovered mechanisms. Summary: The exact molecular machinery underlying puberty initiation in humans is under intensive investigation. In this review, we summarize research evidence in the field, while emphasizing the areas of uncertainty and underlining the impact of current information on the evolving theory regarding this fascinating phenomenon.